2021
DOI: 10.1111/oik.08381
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and timing of resource pulses interact to affect plant invasion

Abstract: Human activities can cause resource fluctuations through reducing uptake by the resident vegetation (e.g. disturbance) or through changing external resource supply (e.g. fertilization). Resource fluctuations often occur as pulses which are low frequency, large magnitude and short duration and now are recognized as an important driver of plant invasions. However, resource pulses often vary dramatically in a number of attributes, yet how these attributes mediate the impacts of resource pulses on plant invasions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…For multiple small pulses, we added Hoagland solution with the following sequence: 5, 75, 40, 80, 35, 5, 65, 20, 35, and 40 ml. The total amount of nutrients was 400 ml of 400% Hoagland solution for all treatments, which is consistent with previous studies (Liu & van Kleunen, 2017; Liu, Zhang, & van Kleunen, 2018; Tao et al, 2021). To eliminate a potential bias in water supply in nutrient treatments, we dissolved Hoagland solution in the water being added to pots to maintain the target volumetric water content.…”
Section: Methodssupporting
confidence: 91%
“…For multiple small pulses, we added Hoagland solution with the following sequence: 5, 75, 40, 80, 35, 5, 65, 20, 35, and 40 ml. The total amount of nutrients was 400 ml of 400% Hoagland solution for all treatments, which is consistent with previous studies (Liu & van Kleunen, 2017; Liu, Zhang, & van Kleunen, 2018; Tao et al, 2021). To eliminate a potential bias in water supply in nutrient treatments, we dissolved Hoagland solution in the water being added to pots to maintain the target volumetric water content.…”
Section: Methodssupporting
confidence: 91%
“…a temporal increase) in resource availability 6 . Although it has become a widely accepted theory in ecology, empirical studies that tested it [7][8][9][10][11][12] have found mixed results. For example, whereas Parepa et al 7 found that a nutrient pulse increased the dominance of an invasive plant, Liu et al 9 showed that a pulsed nutrient supply decreased the dominance of invasive alien plants.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of native plants by one nonnative species may thus result in an overall facilitative effect for another non-native species (Allen et al, 2021;Flory & Bauer, 2014). Therefore, considering the increasing number of non-natives accumulating in native communities (Kuebbing et al, 2013;van Kleunen et al, 2015), native species should be included in future studies to test how resource pulse impacts interactions among non-natives. Moreover, the impact of resource pulses on individual growth, population dynamics, and community structure can vary significantly depending on the characteristics of the nutrient inputs (Felton et al, 2020;Post & Knapp, 2020;Sher et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of resource pulses on individual growth, population dynamics, and community structure can vary significantly depending on the characteristics of the nutrient inputs (Felton et al, 2020; Post & Knapp, 2020; Sher et al, 2004). For example, Tao et al (2021) demonstrated that, compared with nutrients supplied at a constant rate, nutrients supplied as a single large pulse increased the proportion of aboveground biomass of non‐native C. canadensis under low nutrient addition magnitude in an artificial native community but decreased the proportion of C. canadensis in a community under high magnitude nutrient additions. Thus, to accurately predict the responses of interactions among non‐natives to resource pulses, it is essential to integrate attributes of resource pulses, such as magnitude and timing, in future studies.…”
Section: Discussionmentioning
confidence: 99%